SISTEM INFORMASI RENTAL KAMERA BERBASIS WEB (STUDI KASUS SC STUDIO) - Linda Apriyanti; Meidi Fransisca Siregar; Endi Gozali (LPPM STMIK BANDUNG, 2022)
The camera rental information system is a system used to enter camera loan transaction data into the database, so that there are no errors when inputting, and making reports so that the results are in accordance with the expected data. In addition to data input and output processes, this information system also stores customer data. With this information system, it is hoped that it can reduce the risk of losing old data that you want to reuse. This information system is also expected to speed up the input and output process which in turn can help admins and customers. The research anddevelopment method used in this research is to use a linear sequential method starting with communication, planning, modeling, construction and deployment.